Bone grafts and bone substitutes in dentistry - Syed Saima; Suhail Majid Jan; Aasim Farooq Shah; Asif Yousuf; Manu Batra (Wolters Kluwer Medknow Publications, 2016)
Bone resorption is a natural phenomenon and can occur due to old age, loss of teeth, prolonged denture wear, or as a result of systemic conditions. For the replacement of teeth by fabrication of prosthesis or the use of implants, a minimum amount of bone density is required. Bone grafting is a method by which bone-deficient areas are built up, with the use of different materials, such as autografts, allografts, alloplasts, and xenografts. Over recent times, the use of frozen bone matrix formulations and synthetic ceramics has been used in greater frequency. This article discusses the use of human bone material (allografts), synthetic materials (alloplasts) and blood components as successful grafting materials. Their use has shown an effective amount of bone formation and proliferation in the defective sites and proves to be a beneficial choice in bringing back lost bone.